2022
DOI: 10.3390/jcm11175186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of on-Table Extubation after Pediatric Cardiac Surgery

Abstract: Background: Enhanced recovery after surgery (ERAS) protocols are utilizing a multidisciplinary approach, reassessing physiology to improve clinical outcomes, reducing length of hospital stay (LOS) stay, resulting in cost reduction. Since its introduction in colorectal surgery. the concept has been utilized in various fields and benefits have been recognized also in adult cardiac surgery. However, ERAS concepts in pediatric cardiac surgery are not yet widely established. Therefore, the aim of the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The authors included only children with AV‐canal defects (21%), non‐restrictive VSDs (39%), and Fallot type of congenital heart disease (40%) for all of whom such protocols are available leading to safe and early (on the table) extubation with superior clinical results. Baehner et al described a significant shorter stay on the pediatric intensive care unit, less inotropes, less fluids and avoidance of prolonged postoperative ventilation in children extubated immediately after surgery for congenital heart disease 8 . The patient cohort in the current study could potentially have been extubated in the operating room without a risk of increased morbidity.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…The authors included only children with AV‐canal defects (21%), non‐restrictive VSDs (39%), and Fallot type of congenital heart disease (40%) for all of whom such protocols are available leading to safe and early (on the table) extubation with superior clinical results. Baehner et al described a significant shorter stay on the pediatric intensive care unit, less inotropes, less fluids and avoidance of prolonged postoperative ventilation in children extubated immediately after surgery for congenital heart disease 8 . The patient cohort in the current study could potentially have been extubated in the operating room without a risk of increased morbidity.…”
mentioning
confidence: 71%
“…Baehner et al described a significant shorter stay on the pediatric intensive care unit, less inotropes, less fluids and avoidance of prolonged postoperative ventilation in children extubated immediately after surgery for congenital heart disease. 8 The patient cohort in the current study could potentially have been extubated in the operating room without a risk of increased morbidity. "On the table" extubation is an increasing practice in pediatric cardiac surgery.…”
mentioning
confidence: 99%
“…Pulmonary hypertension or a better risk for possible postoperative pulmonary hypertension crisis was often cited as an argument for prolonged postoperative ventilation in children after cardiac surgery. However, a recent study revealed that the reasons for reintubation after extubation in the operating room following pediatric cardiac surgery were bleeding or insufficient respiration but not pulmonary hypertension crisis [ 18 ].…”
Section: Early Extubation and Pulmonary Hypertensionmentioning
confidence: 99%
“…Broadly speaking for those who have undergone CPB surgical cases, those with minimal inotropic and ventilatory requirements should be considered candidates for early extubation (in the operating room or within 6 hours after surgery), even those with pulmonary hypertension. [58][59][60][61] A meta-analysis of studies thus far found that early extubation in pediatric cardiac surgical patients is not associated with adverse outcomes and may reduce in-hospital morbidity and mortality. 61 Most coarctation patients who present for surgery in stable condition are able to be extubated after surgical repair.…”
Section: Mitral and Subaortic Stenosis Repairmentioning
confidence: 99%